Alleviation of salt stress using exogenous proline on a citrus cell line - Lima Costa, Maria Emília (2010)
Salinity constitutes an important abiotic problem since ancient times, world-wide, for it leads to a decrease in productivity of crops with agronomic value. Under salt stress conditions, plant cells develop strategies to cope with Na+ and Cl-, including exclusion and compartmentalisation, induction of antioxidant enzymatic systems and compatible solutes accumulation, such as proline. The precise function of this osmolyte still remains unclear. Proline may act on osmotic adjustment, as a free radical scavenger, protecting enzymes and avoiding DNA damages. It has been also suggested the role of proline in prevention of lipid peroxidation and as a signalling/regulatory molecule. A salt-sensitive Citrus sinensis ‘Valencia late’ cell line has a smaller growth rate and accumulates proline in the presence of NaCl (>200 mM). The addition of external proline to this cell line was evaluated in terms of cell metabolism. A positive influence on the relieve of salt stress symptoms due to the presence of exogenous proline 5 mM and 100 mM NaCl was obtained, with increased growth of this salt sensitive citrus cell line.